Novel Prodiginine Derivatives Demonstrate Bioactivities on Plants, Nematodes, and Fungi - Habash, Samer S.; Brass, Hannah U. C.; Klein, Andreas S.; Klebl, David P.; Weber, Tim Moritz; Classen, Thomas; Pietruszka, Jörg; Grundler, Florian M. W.; Schleker, A. Sylvia S. (Frontiers in Plant Science, 2020)
Bacterial metabolites represent an invaluable source of bioactive molecules which can be used as such or serve as chemical frameworks for developing new antimicrobial compounds for various applications including crop protection against pathogens. Prodiginines are tripyrrolic, red-colored compounds produced by many bacterial species. Recently, due to the use of chemical-, bio- or mutasynthesis, a novel group of prodiginines was generated. In our study, we perform different assays to evaluate the effects of prodigiosin and five derivatives on nematodes and plant pathogenic fungi as well as on plant development. Our results showed that prodigiosin and the derivatives were active against the bacterial feeding nematode Caenorhabditis elegans in a concentration- and derivative-dependent manner while a direct effect on infective juveniles of the plant parasitic nematode Heterodera schachtii was observed for prodigiosin only. All compounds were found to be active against the plant pathogenic fungi Phoma lingam and Sclerotinia sclerotiorum. Efficacy varied depending on compound concentration and chemical structure. We observed that prodigiosin (1), the 12 ring- (9), and hexenol (10) derivatives are neutral or even positive for growth of Arabidopsis thaliana depending on the applied compound concentration, whereas other derivatives appear to be suppressive. Our infection assays revealed that the total number of developed H. schachtii individuals on A. thaliana was decreased to 50 % in the presence of compounds 1 or 9. Furthermore, female nematodes and their associated syncytia were smaller in size. Prodiginines seem to indirectly inhibit H. schachtii parasitism of the plant. Further research is needed to elucidate their mode of action. Our results indicate that prodiginines are promising metabolites that have the potential to be developed into novel antinematodal and antifungal agents.